SISWA AKTIF, SEHAT DAN BERPRESTASI: EDUKASI POSISI ERGONOMIS DUDUK DAN MENULIS YANG BAIK SAAT BELAJAR - Hunowu, Sri Yulian; Bergita Dumar; Sartika; Indra (Jurnal Pengabdian, 2025)
Non-ergonomic sitting and writing positions can cause musculoskeletal disorders and reduce students’ learning concentration. Education on the importance of correct body posture during study is essential to be implemented from an early age. This community service activity aims to increase the awareness and understanding of elementary school students about the importance of applying ergonomic principles in proper sitting and writing positions during the learning process to support long-term health and comfort. This activity was carried out at a vocational high school in Gorontalo City using lecture and demonstration methods. The service activity proceeded smoothly and showed an improvement in students’ understanding of correct and comfortable sitting and writing positions in the school environment. Keywords: Ergonomic Sitting Position, Proper Writing Position